Techniques To Create Customised Documents And Android Apps From latex Files And Impact Of Developed Android Applications - Chetan Shirore (Journal of Advanced Zoology, 2023)
There are several ICT tools to teach Mathematics. A vast amount of e-content is available for higher mathematics. One of the handiest ICT tools is smartphones for students and teachers of mathematics. A significant proportion of smartphone users are android based. LaTeX is one of the most widely used typesetting systems for scientific publications. There are no easy ways to create Android Apps from LaTeX files. The research aims to present techniques we developed for creating android apps from LaTeX files. We have developed unique techniques to create Android Apps from LaTeX files. The outline of developed techniques and their impact are discussed in this research paper.